Do male managers increase risk-taking of female teams? Evidence from the NCAA - Boheim, R.; Freudenthaler, C.; Lackner, M. (Johannes Keppler Universität, 2019)
We analyze the e ect of the coach's gender on risk-taking in women sports teams using data taken from National Collegiate Athletic Association (NCAA) basketball games. We nd that the coach's gender has a sizable and signi cant e ect on risk-taking, a nding that is robust to several empirical strategies, including an instrumental variable approach. In particular, we nd that risk-taking among teams with a male head coach is 5 percentage points greater than that in teams with a female head coach. This gap is persistent over time and across intermediate game standings. The fact that risk-taking has a signi cantly positive e ect on game success suggests that female coaches should be more risk-taking.